Dependency and Development in the Era of BRICS: A Critical Examination of the New Development Bank’s Role in South Africa - Dian Venita Sary; Putri Ameliya (Institute of International Studies, 2026)
The New Development Bank (NDB’s) role in development projects in South Africa is critically examined in this article regarding dependency dynamics duirng the BRICS cooperative era. The NDB is often seen as an alternative to global financial institutions dominated by Western powers. However, its operations raise questions about whether the bank is truly capable of challenging Western dominance and realizing equitable development, or if it simply duplicates existing dependencies and creates the new ones. By examining NDB financing in transportation, renewable energy, and water management projects, this study highlights how NDB-funded development interacts with ongoing power imbalances and economic vulnerabilities. The article uses a qualitative-descriptive research method by theory-driven content analysis from literature review and project report and academic publication with a case study approach to analyze South Africa’s dependency dynamics under NDB’s financing. Result of this article show that although the NDB provides a broader and more flexible financing system for South Africa, in practice, the lending conditions, project establishment requirements, and governance structure applied still have the potential to place South Africa in a position that is vulnerable to the risk of new dependencies, in this case with Tiongkok. This study contributes to the broader discourse on global south development, global political economy, and the application of dependency theory in a multipolar world.